Activation of membrane progesterone receptors (mPRs) represents a novel tool for prolactin inhibition in animal models of prolactinomas - Camilletti, María Andrea (2019)
Membrane progesterone receptors (mPRs) are known to mediate rapid non-genomic progesterone (P4) effects in different cell types. We recently demonstrated that mPRα is highly expressed in the rat pituitary, being primarily localized in lactotrophs and mPRα/β activation leads to a decrease in prolactin (PRL) secretion. The role of P4 in prolactinoma development remains unclear. In the present work, pituitary expression of mPRs was studied in a well-known model of prolactinoma, transgenic D2 dopamine receptor-deficient mice (Drd2 KO). Expression of mPRs and the classical P4 receptor (nPR) was found significantly decreased in female Drd2 KO pituitaries compared to their WT counterparts. However, the relative proportion of mPRα and mPRβ was increased (about 60% of total pituitary PRs) in tumoral pituitaries. This elevated proportion of mPR to total PR was also observed in other two animal models of prolactinoma. We also found gender differences: male pituitaries express higher levels of mPRs than females, without genotype differences. Males do not develop prolactinoma, even in the absence of dopaminergic inhibition. Finally, as P4 also regulates PRL secretion indirectly by acting on dopaminergic neurons, we studied mPR expression in hypothalamus. We found that the hypothalamus has high expression of mPRs, representing about 80% of total PRs, without genotype or gender differences. Interestingly, the mPR agonist increased dopamine release in hypothalamic explants. Taken together these findings suggest mPRα/β activation could represent a potential tool for hyperprolactinemic patients, especially those that present resistance to dopaminergic drugs.